ANALISIS FAKTOR KESADARAN BERASURANSI TERHADAP KESEJAHTERAAN TENAGA KERJA DI KOTA DENPASAR - Santhi, Luh Gde Bintang Kumara; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
Insurance is the fruit of the human mind and mind to achieve a situation that can meet their needs, especially for their essential needs, including feeling safe and protected. Health insurance will help availability for all the needs of doctor's fees, medicines, hospitalization, up to surgery. If at any time we fall ill, it is the insurance company that will bear the medical expenses, according to the contract or agreement. The purpose of this study was to analyze the effect of age, gender, education level, and income on insurance awareness in Denpasar City partially and simultaneously. This research was conducted on workers in Denpasar City with a total sample of 100 respondents with a questionnaire instrument. The data analysis technique used in this study is logit. Age, gender, education level and income variables simultaneously influence insurance awareness. Age, gender, education level, income have a significant influence on awareness of insurance. The Health Insurance Association is also expected to be able to provide strict laws for agents and companies who provide false presentations and information to the public.